2021
DOI: 10.1097/j.pain.0000000000002510
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of blood biomarkers in patients with fibromyalgia: a systematic review with meta-analysis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 99 publications
1
40
1
1
Order By: Relevance
“…Although we used a high sensitivity method to measure plasma cytokine concentrations, the short half-life, interaction with biological inhibitors, and protein binding in the circulatory system may limit their quantification. 37,48 It is known that technical variability, such as commercial kits, using serum versus plasma, using different anticoagulants (citrate, heparin, EDTA), freezing-thawing cycles, assay methods (enzyme-linked immunosorbent assay, bead-base multiplex), are important limitations to consider when establishing normal reference range and cut-off values of blood cytokines for clinical diagnosis utility. 35,37,38 Despite these limitations, putative cytokine changes in response to distinct SMT force magnitudes might aid in the identification of potential objective biomarker candidates of treatment response and thereby lend clinical utility.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we used a high sensitivity method to measure plasma cytokine concentrations, the short half-life, interaction with biological inhibitors, and protein binding in the circulatory system may limit their quantification. 37,48 It is known that technical variability, such as commercial kits, using serum versus plasma, using different anticoagulants (citrate, heparin, EDTA), freezing-thawing cycles, assay methods (enzyme-linked immunosorbent assay, bead-base multiplex), are important limitations to consider when establishing normal reference range and cut-off values of blood cytokines for clinical diagnosis utility. 35,37,38 Despite these limitations, putative cytokine changes in response to distinct SMT force magnitudes might aid in the identification of potential objective biomarker candidates of treatment response and thereby lend clinical utility.…”
Section: Limitationsmentioning
confidence: 99%
“…Our recent systematic review and meta-analysis demonstrated that blood cytokine concentration is highly variable, even with a population with the same diagnosis. 48 As a result, targeting young, healthy adults enables us to better observe the effects of distinct SMT force magnitudes on systemic putative biomarkers without the interference of underlying pathology that may likely be interfering in the cytokine milieu. Therefore, studying healthy young asymptomatic samples is an important first step that aids to establish a baseline response on blood cytokines in distinct SMT force magnitudes.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for objective biomarkers for diagnosis (case identification), phenotyping (subgroup identification), and prognosis (treatment response and follow-up) in FM. Comparisons between protein serums levels, genetic factors, and neuroimaging biomarkers have been described in the literature based on several potential mechanisms related to FM, such as central sensitization, immune system implications, and alterations in neurotransmitters 3 , 5 , 7 , 8 . However, further research is necessary to validate these potential biomarkers 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This position causes serious problems for the patient and the health care system, by slowing down diagnostic confirmation, increasing the consumption of health care resources by patients, leading to non-recognition of the degree of disability, and increasing the potential biopsychosocial deterioration caused by this disease (11)(12)(13)(14)(15). Being aware of this scenario and of the great controversies surrounding fibromyalgia (2,16,17), several investigations have been performed to find new information that provides a greater understanding of the disease (18)(19)(20)(21)(22). In this context, validation studies have focused on the creation of tools that facilitate the identification of patients with fibromyalgia (23)(24)(25)(26) from pri-mary care consultations.…”
Section: Introductionmentioning
confidence: 99%